2001
DOI: 10.1002/1097-0320(20010601)44:2<113::aid-cyto1089>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chromatin compactness and dye uptake for in situ chromatin stained with DAPI

Abstract: Background This study investigated the relationship between chromatin compactness, which is directly related to chromatin condensation, and DAPI uptake. Materials and Methods For the structural characterization of in situ chromatin, we used fluorescence microscopy and differential scanning calorimetry on calf thymocytes. The compactness of nuclear chromatin was altered by permeabilizing native cells with NP40 detergent. A time‐dependent analysis of detergent effects was performed by acquiring nuclear images at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…After permeabilization in 0.05% Triton X-100 solution (Sigma), ECs were stained with 25 µg ml − 1 DAPI and a stack of nuclear images at different focal positions along the z axis (0.15 µm intervals) were acquired in confocal scanning microscopy. To obtain quantitative information, shading correction and dark image substraction were applied in MATLAB to each image 38 and a constrained deconvolution in NIS Elements AR software was used to sharpen the image 56 . After normalizing for time exposure, the integrated fluorescence intensity was calculated as the sum of the intensity of each pixel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After permeabilization in 0.05% Triton X-100 solution (Sigma), ECs were stained with 25 µg ml − 1 DAPI and a stack of nuclear images at different focal positions along the z axis (0.15 µm intervals) were acquired in confocal scanning microscopy. To obtain quantitative information, shading correction and dark image substraction were applied in MATLAB to each image 38 and a constrained deconvolution in NIS Elements AR software was used to sharpen the image 56 . After normalizing for time exposure, the integrated fluorescence intensity was calculated as the sum of the intensity of each pixel.…”
Section: Methodsmentioning
confidence: 99%
“…After normalizing for time exposure, the integrated fluorescence intensity was calculated as the sum of the intensity of each pixel. The total fluorescence intensity was then divided by the nuclear volume to obtain the average spatial density, which correlates with the average chromatin packing ratio 56,57 , and as such is indicative of chromatin condensation. The proliferative activity in shape-engineered ECs has been investigated by detecting the incorporation of BrdU into cellular DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Here we used the average 4′, 6-diamidino-2-phenylindole (DAPI) spatial density to assess global changes in chromatin condensation because the density of DAPI staining in nuclei increases with the chromatin packing ratio [36,37]. We found that S1 cells in 3D lrECM had higher DAPI density than cells cultured in 2D (Fig.…”
Section: Culturing Cells In 3d Lrecm Induces Alterations In Cellular mentioning
confidence: 99%
“…To assess the nuclear volume, a common intensity threshold was established to define the edge of the nuclei in each confocal section and calculate the enclosed area. The total fluorescence intensity was divided by the nuclear volume to obtain the average dye spatial density, which correlates with the average chromatin packing ratio (Mascetti et al 2001). All image processing was performed using Image J software.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…In the literature, there are many examples of use of CCD cameras for detecting fluorescent labelledDeoxyribonucleicAcid DNAsorsomeexpressions on the stained, fixed or live cells. Some examples to that is imaging of growing DNA chains [2], real-time detection of DNA hybridization to DNA microarrays [3], monitoring of anticancer effects of some specific agents [4], examining of cell polarity on stained, fixed and live cells [5] and obtaining quantitative information about the chromatin-DNA distribution inside the nucleus [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%